Redefining language and literature learning in the transformation era - Suryaman, Maman; Wiyatmi, W.; Pujiono, Setyawan; Kristiyani, Ary (Indonesian Journal of Applied Linguistics, 2021)
The study was aimed at redefining the learning of language and literature from the perspective of media use in the lesson planning and implementation and students’ responses towards language and literature learning. The subjects of the study were teachers and students of state junior high schools in a regency in Yogyakarta Province. The subjects were taken in three stages, first, with the cluster technique: the eastern, western, central, and northern zones, and second, with the school strata technique: as excellent, moderate, and low. The choice of strata technique was determined based on the results of the 2017 National Exam score ranking. Third, the selection of schools and classes was made randomly. Primary data were obtained from observation, interview, and document analysis; secondary data were obtained from a questionnaire. Results can be described as follows. First, media use designed in the lesson plan included conventional, new, and audio-visual media. Second, media use in the carrying out of the lesson was realized by the teachers in the forms of conventional visual and audio-visual media. Third, students gave fair responses to the use of instructional media in language and literature learning. In the low-coded schools, the use of media designed in the lesson plans was more varied than that of the moderate- and excellent-coded schools; the most preferred new visual media were PowerPoint. In moderate- and low-coded schools, instructional media were shown to have positive impacts on student activity in learning; namely, students were more active because learning was more fun. Contradictorily, instructional media did not have positive impacts in excellent-coded schools on student activity in learning; namely, students were less active because learning was considered unpleasant. As seen from the perspective of the transformational era, no teacher had used interactive digital media.